Effects of recent cooling in the Antarctic Peninsula on snow density and surface mass balance - Recio Blitz, Cayetana del Pilar; Navarro Valero, Francisco José; Otero García, Jaime; Lapazaran Izargain, Javier Jesús; González Herrero, Sergi (E.T.S.I. Telecomunicación (UPM), 2018)
The Antarctic Peninsula region has experienced a recent cooling for about 15 years since the beginning of the 21st century. In Livingston Island, this cooling has been of 0.8°C over the 12-yr period 2004–2016, and of 1.0°C for the summer average temperatures over the same period. In this paper, we analyse whether this observed cooling has implied a significant change in the density of the snowpack covering Hurd and Johnsons glaciers, and whether such a density change has had, by itself, a noticeable impact in the calculated surface mass balance. Our results indicate a decrease in the snow density by 22 kg m-3 over the study period. The density changes are shown to be correlated with the summer temperature changes. We show that this observed decrease in density does not have an appreciable effect on the calculated surface mass balance, as the corresponding changes are below the usual error range of the surface mass balance estimates. This relieves us from the need of detailed and time-consuming snow density measurements at every mass-balance campaign.